Transformasi Pengajaran: Pelatihan Kreativitas dan Inovasi Guru dalam Era Kurikulum Merdeka - Ii, Tri Juli Hajani; Mandasari, Novianti (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
The Merdeka Curriculum is an educational innovation that gives educators the freedom to create quality learning experiences tailored to students' needs and learning environments. To effectively implement this curriculum, creative and innovative educators are essential. This community service project aims to enhance teachers' competencies in teaching creativity and innovation through training conducted at the KKG Cluster 5 in North Curup District, Rejang Lebong Regency. The methods employed include lectures, question-and-answer sessions, and practical exercises, covering topics such as creative and innovative thinking, recognizing students' abilities, classroom management, technology utilization, and parental involvement in learning. The training results show high enthusiasm from participants and improved understanding of implementing creative and innovative learning. Teachers gained new insights into the use of learning media, including the utilization of smartphones and other digital technologies. They also acquired a better understanding of the importance of involving parents in the learning process. This activity is expected to encourage a transformation in teaching practices, making them more engaging, effective, and aligned with the demands of the Merdeka Curriculum, ultimately improving the quality of education in the region.   Keywords: merdeka curriculum; teacher creativity; learning innovation; teacher training; teaching transformation